PEOPLE LIVING WITH DISABILITIES AND SOCIO- ECONOMIC WELL-BEING IN GBOKO LOCAL GOVERNMENT AREA, BENUE STATE, NIGERIA - Ierve, Nguavese; Akpovye Bage-John, Dorothy (African Journal of Social and Behavioural Sciences, 2026)
This study investigated People Living with Disabilities (PLWDs) and their Socio- economic Well-being with specific emphasis on the effect of Visual impairment on the Socio- economic Wellbeing of PLWDs, and the influence of walking impairment on the Socio-economic Wellbeing of PLWDs in Gboko Local Government Area of Benue State, Nigeria. The study adopted Medical Model of Disability and Eugenics and the Social Model of Disability as its theoretical framework. Cross-sectional survey design was adopted for the study, and the multistage sampling technique was used to reach the respondents. Primary data was collected using questionnaires and an interview guide. Data was processed and analyzed using Statistical Packages for Social Sciences (SPSS) version 27. The results showed that 96.3% of the respondents agreed that people with partial or complete loss of sight struggle to complete formal education, and that people with walking disabilities face discrimination in social gatherings, 92.1% of respondents believe that having a sight-related condition affects self-esteem. The study concludes that disabilities not only limit access to education and employment opportunities but also intensify social exclusion for PLWDs in Gboko Local Government Area. The study therefore recommends improved implementation of existing laws that promote social inclusion, provision of adaptive learning materials in educational institutions, creation of adaptive workspaces, and eradication of biases against disabled persons in Gboko Local Government Area of Benue State, Nigeria.